2020
DOI: 10.1186/s40793-020-0353-3
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the effects of tropical land use conversion on the soil microbiome

Abstract: Background: The consequences of deforestation and agricultural treatments are complex and affect all trophic levels. Changes of microbial community structure and composition associated with rainforest conversion to managed systems such as rubber and oil palm plantations have been shown by 16S rRNA gene analysis previously, but functional profile shifts have been rarely addressed. In this study, we analysed the effects of rainforest conversion to different converted land use systems, including agroforestry ("ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 85 publications
(162 reference statements)
4
26
0
Order By: Relevance
“…In our study, citrus planting caused a decline in soil pH, resulting in decreases in soil bacterial diversity. Soil pH has been widely accepted as the most important factor that affects soil bacterial/fungal community composition (Lauber et al The conversion of natural vegetation land to citrus orchards altered the soil microbial community composition, which is in agreement with the results in previous studies (37). Proteobacteria (Alphaproteobacteria and Deltaproteobacteria) and Acidobacteria (Subgroup_6 and Subgroup_4) were negatively influenced by the conversion, which might be due to the decline in soil pH and SOC.…”
Section: Citrus Planting Reduces Soil Microbial Communitiessupporting
confidence: 88%
See 4 more Smart Citations
“…In our study, citrus planting caused a decline in soil pH, resulting in decreases in soil bacterial diversity. Soil pH has been widely accepted as the most important factor that affects soil bacterial/fungal community composition (Lauber et al The conversion of natural vegetation land to citrus orchards altered the soil microbial community composition, which is in agreement with the results in previous studies (37). Proteobacteria (Alphaproteobacteria and Deltaproteobacteria) and Acidobacteria (Subgroup_6 and Subgroup_4) were negatively influenced by the conversion, which might be due to the decline in soil pH and SOC.…”
Section: Citrus Planting Reduces Soil Microbial Communitiessupporting
confidence: 88%
“…Conversion from natural to agricultural ecosystems has been considered as the most important driving force to regulate soil microbial communities (37). In this study, citrus planting was found to reduce soil bacterial and fungal diversity in a time dependent manner.…”
Section: Citrus Planting Reduces Soil Microbial Communitiesmentioning
confidence: 83%
See 3 more Smart Citations